54 Novel formin homology 2 domain containing 3 (FHOD3) mutations associated with the pathogenesis of hypertrophic cardiomyopathy (HCM) in an irish population. (16th October 2019) - Carron, J; McGorrian, C; Galvin, J; Gallagher, M; O'Brien, J
Abstract : Background: The genetic cause of hypertrophic cardiomyopathy (HCM) remains unexplained in a substantial proportion of cases. Recent large sequencing studies suggest that, although not previously implicated, FHOD3 (a Formin protein responsible for sarcomere assembly) may have a role in the pathogenesis of HCM, particularly variants affecting a conserved small coil-coiled domain (amino acids 622 to 655). Aim: To investigate the relationship between novel FHOD3 mutations, previously classified as variants of uncertain significance (American College of Medical Genetics ACMG Class III), and the development of HCM in an Irish cohort. Methods: A single center review of HCM probands carrying mutations in the FHOD3 gene was conducted. All existing HCM patients from the Family Heart Screening Clinic (FHSC) database were retrospectively reviewed. Frequency of FHOD3 mutations among the center's HCM cohort, segregation among family members where available, as well as clinical characteristics of gene carrying patients were also reviewed. All genetic analysis was conducted via the same internationally validated next generation sequencing lab. Results: Of 367 HCM probands identified in our center, 9 (2.45%) were found to have ACMG Class III mutations affecting the FHOD3 gene. Of these, 2 were found to have additional gene mutations more strongly associated with the development of HCM (ACMG Class IV & V), affecting the MYH7 and MYBPC3 genes respectively. Five of these 9 probands (56%) displayed the same p.Arg637Gln mutation (2 of whom displayed additional confirmed pathogenic mutations), while the remaining 4 (44%) tested positive for the same p.Ile648Thr residue alteration. Both of these are rare mutations, found to be present in <1% of controls in previous large sequencing studies. Among probands with the p.Ile648Thr mutation, co-segregation was confirmed in one family, another first-degree relative in the same family having suffered a sudden cardiac death (with HCM confirmed on autopsy) prior to the availability of sample storage for post-mortem gene sequencing. In those with the p.Arg367Gln mutation, a strong family history was observed in two separate families, 4 first-degree members having a confirmed HCM diagnosis. Carriers of both mutation types displayed varying degrees of disease severity (table 1). Conclusions: FHOD3 is a novel gene, recently implicated in the pathogenesis of HCM, though not previously well described in the literature as disease causing. The HCM population in our center demonstrates rates of FHOD3 carriers similar to those described in recent publication (1–2%) and all affected patients carry variants affecting the suspected conserved small coil-coiled domain (amino-acids 622–625). The specific residue alterations described in our population however have not been reported in prior studies due to incomplete co-segregation, though may prove clinically relevant in the future. Given the difficulty predicting the degree of pathogenicity of novel non-truncating variants in sarcomeric genes, complete co-segregation analysis is necessary to fully determine the role of these novel FHOD3 variants in our HCM population.